Using CFA for the Alternative Quality Assurance Evaluation Model (QAEM) For National Universities Commission (NUC) of the Federal Republic of Nigeria - Bolaji, Bojuwon Yusuf; Mohd Ali, Hairuddin (2013)
“If you can’t measure it, you can’t manage it” Deming, (2010) and Drucker (2010), (2006), (2009), Kaplan, (2009) and Patterson (2008) who said, “If you can’t measure it, you can’t manage it. The above quotations are views from different authors who are related to the research that is conducted on Nigerian University System (NUS) of education. The structures and content of today’s educational system in Nigeria are derived largely from the well acclaimed 1969 outcome of the curriculum conference which provided the conceptual and doctrinal framework by which to build a true great Nigeria. It thus metamorphosed or gave birth to the publication of the National Policy on Education (NPE) of the Federal Republic of Nigeria and was launched in 1977; and revised in 1981, 1998 and most recently, in 2004. The paper is to examine the construct validity of the of the alternative QAEM NUC construct. The paper examined the dimensionality of the model using CFAto checked the fitness of the data for the alternative QAEM accreditation scale constructs for NUES. The paper employs a quantitative approach to survey the alternative QAEM (SCON) parameters through the process of validation that involve Confirmatory Factor Analysis. The finding demonstrated that the Alternative QAEM accreditation scale construct for NUC revealed that the threshold value recommended supported the sample of the data collected.